Features of seafarers employment contracts - Iryna Pidpala (Kazimierz Wielki University, 2019)
This article has explored the features of the employment contract of seafarers. The parties to this contract are the seafarer and the shipowner, who have their own subjective rights and obligations, which are defined as contracts of tax and labor law in general. Legal regulation of contracts is carried out by both international and labor legislation of the sailor's country. Objective features of seafarers' labor relations necessitate the establishment of special norms regulating working crew members of seagoing vessels, because they perform the labor functions of seafarers, attract grounds for sectoral differentiation of legal regulation of their work. Certainly, seafarers must be very attentive when concluding a contract, pay attention to the minimum list of clauses of the employment agreement, do not sign an incomplete agreement, make sure about the specified wages, compensation payments, and other conditions, show legal literacy.